The Place of Music in Quranic Recitation (American Journal of Islam and Society, 1999)
This paper revisits the debate on the rhythmic recitation of the Quran.It examines the arguments made by those who favor rhythmic recitationand those who oppose it by scrutinizing their Quranic and traditionalsources. The paper examines all the ahadith and the Quranic ayahs thatrelate to the subject and concludes that as long as the rules of tajwid arefollowed it is permissible to embellish the recitation of the Quran withrhythm as well as modulated voice.